Intra-Operative Experience using Magnetic Resonance Imaging (MRI) Based Patient Specific Cutting Guides during Total Knee Arthroplasty - Albrecht, Ryan K.; Chong, Alexander C.M.; Wooley, Paul H.; Bhargava, Tarun (Kansas Journal of Medicine, 2016)
Background. The incidence of malalignment in total knee arthroplasty (TKA) using conventional instrument has been reported as high as 25%. A relatively new TKA system involves the use of a preoperative magnetic resonance image (MRI) to obtain accurate implant placement more consistently. For broad acceptance of this new technique, it is crucial to analyze the initial intra-operative experience. The specific aim of this study was to evaluate the initial intra-operative experience of a single surgeon using this new technique. Methods. A total of 15 knees (12 patients: 6 female and 6 male) were reviewed from TKA procedures using the selected manufacturer’s patient specific cutting guides between January 2011 and April 2013 at a single institution. Patient demographic and specific parameters and intra-operative alterations of component positioning were recorded and evaluated. Results. The preoperative plan was able to predict correctly the size of the implanted femoral component in 87% (n = 13) and tibial component in 80% (n = 12) of the cases. However, 60% (n = 9) of cases required additional intra-operative corrections on femoral resection, and 73% (n = 11) required an additional 2 - 4 mm correction on the tibial proximal resection. Twenty percent (n = 3) required additional tibial varus/valgus correction, but there were no tibial slope corrections for any of the 15 cases. Conclusions. The initial intra-operative experience of a single surgeon using current patient specific cutting guides for a selected manufacturer to align femoral and tibial components during TKA has raised some concerns. We agreed with previous studies that caution should be taken when using patient specific cutting guides without supportive data. The findings of this study provided additional evidence to contest the accuracy of patient specific cutting guides with respect to the initial experience of an orthopaedic surgeon who is trained in total joint replacement. The results provided more evidence to assist orthopaedic surgeons in the decision of whether to use these patient specific systems versus conventional TKA methods. KS J Med 2016;9(2):22-26.